2006
DOI: 10.1021/es0524301
|View full text |Cite
|
Sign up to set email alerts
|

Secondary Organic Aerosol Formation from Isoprene Photooxidation

Abstract: Blank runs. Irradiation of the chambers in the absence of isoprene is always found to lead to negligible aerosol growth. Prior to the start of the experiment (introduction of reagents), the chambers are relatively particle-free, with number densities of <100 particles/cm 3 , corresponding to volume densities below 0.2 µ m 3 /cm 3 . Irradiation of ~3 ppm H 2 O 2 leads to no increase in particle number or volume, as measured by the DMA.In the presence of ammonium sulfate seed, which provides surface area for the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

67
849
10
2

Year Published

2008
2008
2017
2017

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 786 publications
(944 citation statements)
references
References 56 publications
67
849
10
2
Order By: Relevance
“…Isoprene is also known to have a small but significant yield of SOA mass formation. Depending on seed aerosol, initial precursor concentration and relative NO x levels, SOA yields in the range of 1-5 % were reported in the literature (Kroll et al, 2005;Dommen et al, 2006;Kroll et al, 2006;Dommen et al, 2009). Including SOA from isoprene in calculations of the global SOA burden increases SOA by factors between 0.5 and 2 depending on scenarios used (Henze and Seinfeld, 2006).…”
Section: Resultsmentioning
confidence: 99%
“…Isoprene is also known to have a small but significant yield of SOA mass formation. Depending on seed aerosol, initial precursor concentration and relative NO x levels, SOA yields in the range of 1-5 % were reported in the literature (Kroll et al, 2005;Dommen et al, 2006;Kroll et al, 2006;Dommen et al, 2009). Including SOA from isoprene in calculations of the global SOA burden increases SOA by factors between 0.5 and 2 depending on scenarios used (Henze and Seinfeld, 2006).…”
Section: Resultsmentioning
confidence: 99%
“…The gas collected in these canisters was analyzed off-line using the gas chromatographic system with several columns and detectors described by Sive et al [2005] and White et al [2010], allowing for accurate quantification of over 100 different VOC compounds. Specifically, a-pinene and isoprene are used as indicators of BVOC precursors to SOA [Hoffmann et al, 1997;Kroll et al, 2006], toluene is used as an indicator of a mixed biogenic-anthropogenic [White et al, 2009] primary aromatic precursor to SOA , and isopropyl nitrate is used as an additional indicator of secondary processing of anthropogenic emissions [deGouw et al, 2005].…”
Section: Measurementsmentioning
confidence: 99%
“…Owing to its high concentration and reactivity with OH radicals, isoprene plays an important role in the photochemistry occurring within the atmospheric boundary layer. Recently, it has been shown that the photooxidation of isoprene leads to the formation of low volatility species that condense to form SOA (Claeys et al, 2004;Edney et al, 2005;Kroll et al, 2005;Dommen et al, 2006;Kroll et al, 2006;Surratt et al, 2006); SOA yields as high as ∼3% have been observed (Kroll et al, 2005;Kroll et al, 2006). Global SOA production from isoprene photooxidation has been estimated to be about 13 Tg yr −1 (Henze et al, 2007).…”
Section: Introductionmentioning
confidence: 99%